Marketing Know-How Transfers by Multinationals: A Case Study in Turkey - Aydin, Nizam; Terpstra, Vern (Journal of International Business Studies, 1981)
This research examines the transfer of marketing know-how by multinational companies to their subsidiaries in Turkey. The nature and extent of the marketing know-how transferred is analyzed, and the mechanisms used for and the variables which appeared to affect such transfers are identified.